Need For Affiliation melalui Kegiatan Cosplay pada Orang-Orang yang Mengalami Trauma - Reni Suryani; Muslimah Zahro Romas; Amin Al Adib (Jurnal Psikologi, 2023)
This research aims to describe the need for affiliation through cosplay activities among people experiencing trauma. A person who has feelings of trauma tries to rise up so that his motivation and desire are high, so he can give rise to initiative, innovation, creativity and inspiration through cosplay activities. Cosplay is an artistic activity that originates from Japan and is currently very popular in several circles. The focus of this research is to determine the motivation to build a person's independence through cosplay activities. To find out the extent of the need for affiliation through cosplay activities in people who have experienced trauma. This research is qualitative research with a case study method. This research involved two informants, namely cosplay players in Yogyakarta. For data collection, observation, interviews, triangulation and projective tests, namely graphics, were used. The interview guide uses motivation factors from Komarudin (2013) including intrinsic motivation and extrinsic motivation and uses the independence aspect of Parker (2005) consisting of responsibility, independence and autonomy which have been developed by researchers. The research results showed that the two cosplay player informants were able to generate motivation to build independence through cosplay activities. This is based on analysis of the results of observations, interviews and triangulation.